Prognostic factors for overall survival in patients with chronic myeloid leukemia treated with imatinib at the National Cancer Institute – Mexico, from 2000 to 2016. (2nd May 2019) - Ylescas‐Soria, Jimena; de la Torre‐Lujan, Alfredo H.; Herrera, Luis A.; Miranda, Daniela; Grimaldo, Flavio; Rivas, Silvia; Cervera, Eduardo; Meneses‐García, Abelardo; Leon-Sarmiento, Fidias E.; Prada, Diddier
Abstract: To determine potential predictors of long‐term survival in a large set of Hispanic (Mexican) patients with chronic myeloid leukemia (CML) treated with imatinib. We conducted an analysis with data from 411 patients with CML treated at the National Cancer Institute – Mexico, between January 2000 and December 2016. We found a median age at diagnosis of 40 years (range: 18‐84 years). The survival rate at 150 months was 82.02%, and we found that phase at diagnosis ( β : 0.447, 95% Confidence Interval [95% CI]: 0.088, 0.806; P  = 0.015), prognostic scales (Sokal [ P  = 0.021] and Hasford [ β : 0.369, 95% CI: 0.049, 0.688; P  = 0.024]) and hematological response at 3 months ( β : 0.717, 95% CI: 0.443, 0.991; P  < 0.001), but not molecular response ( P  = 0.834 for 6 months, P  = 0.927 for 12 months, P  = 0.250 for 18 months), were independently associated with overall survival. Survival analysis in subsets, according to the initial phase (chronic, accelerated and blastic phase) did not show any effect according to prognostic scales ( P  > 0.05). Mexican patients with CML have repeatedly been diagnosed at earlier ages. Prognostic factors in CML may differ according to the ethnic or geographical context. We found that phase at diagnosis, prognostic scale and hematological response at 3 months were independent predictors of survival. Abstract : We conducted an overall survival analysis with data from 411 patients with CML treated at the National Cancer Institute – Mexico, between January 2000 and December 2016. Phase at diagnosis, prognostic scale and hematological response at 3 months were independent predictors of survival in Mexican patients with CML treated with Imatinib.